Data Management & Data Modelling - Kadam, Hrishikesh Bhimsen (ATLAS SkillTech University, 2025)
During my time with Wellington football club Mumbai as a business analyst, I was involved in making use of data analytics thinking and contributing towards the improvement of the club performance. I was responsible for data collection as well as data cleaning and data analysis pertaining to player performance, strategies adopted by the team as well as the fans.In doing data analysis, I created a very strong data warehouse that included players tracking systems, match information, and fan data for more efficient analysis of fans’ behavior. Using Python, I computerized data integration so that it was possible to update the data warehouse without any manual processes.Through the performance data analysis, it was possible to make recommendations on how players were performing in a particular marketing strategy desired improvement, or which specific area of the team tactics required adjustment. This analysis supported the coaching staff and the management team in making decisions that would have positive effects on the competitiveness of the club.
Project Report on Data Management & Data Modelling (2023-2025) Under the Guidance of Prof. Shashikant Patil
Keywords: data analytics; club performance; coaching staff; management; competitiveness; business analyst